Inspiring, Exploring, Activating and Organizing: A Framework for Improving Communication Skills and Product Knowledge in Call Center - Shoaib, Syed Muhammad (Asian Journal of Social Sciences and Management Studies, 2017)
The rapid growth of call centers and customer dependency on call center puts very high demands and standards for the call center management in terms of customer satisfaction. Beside operational management areas like forecasting, scheduling, recruitment and hiring, training plays a significant role in achieving customer satisfaction from call centers. This paper deals with the training in a call center and suggest a framework for training to improve customer satisfaction by improving product knowledge and communication skills of call center agents. The traditional training programs in call centers heavily focuses on forced learning methods and traditional lecture base approach. This work provides a framework and establishes four principles to reform training program in order to improve communication skills and product knowledge of call center agents. The first principle “Inspiring” focuses on personal and professional development of call center agent through call center. The second principle “Exploring” focuses on self-learning through designed explorations ,the third principle “Activating” focuses on activity base learning for communications skills and product knowledge in call centers and the last principle “Organizing” aims at incorporation of these principals into training programs and in training curriculum for effective training execution according to the guidelines provided in the framework.